Dynamics of Inhaled Tobramycin Concentration in Blood and Bronchoalveolar Lavage Fluid during Nosocomial Pneumonia (Preliminary Report) - A. N. Kuzovlev; A. K. Shabanov; I. А. Tyurin (Общая реаниматология)
This study was aimed to evaluate the dynamics of inhaled tobramycin concentration in bronchoalveolar lavage fluid and blood in victims with nosocomial pneumonia.Materials and Methods. The study is presented as a series of clinical observations: 5 patients with severe concomitant craniocerebral injury were included, who were treated in the general resuscitation unit (men 4 (87.5%), women 1 (12.5%); age 36Ѓ}12 years; Injury Severity Score (ISS) 40.9Ѓ}8.3; acute blood loss volume 2356Ѓ}997 ml; mean bed-days 12.50 days; mortality 16.7%). Statistical analysis of data obtained was carried out using Statistica 10.0 software. Difference was considered significant at p<0.05.Results. The dynamics of tobramycin concentrations was as follows: 1 hr. blood/BAL 0.96Ѓ}0.44 μg/ml / 49.6 μg/ml; 3 hrs. blood/BAL 0.98Ѓ}0.82 μg/ml / 15.5 μg/ml; 5 hrs. blood/BAL 0.79Ѓ}0.83 μg/ml / 3.5 μg/ml. Conclusion.The results obtained confirm significant local concentrations of tobramycin in sputum and low in blood, which corresponds to the results of pharmacokinetic studies and clinical studies of inhaled tobramycin efficacy. At present, gathering of material for the study continues.